Patterns of group home culture in organisations supporting people with intellectual disabilities: A cross-sectional study. Issue 3 (3rd July 2022) - Humphreys, Lincoln; Bigby, Christine; Iacono, Teresa; Bould, Em
ABSTRACT: Background: Organisational culture in group homes for people with intellectual disabilities has been identified as an influence on service delivery and staff behaviour. The aim was to examine patterns of culture across group homes in disability organisations. Method: The Group Home Culture Scale (GHCS) was used to measure staff perceptions of culture. Data were available from 260 staff who worked across 58 group homes managed by eight organisations. Using scatterplots and measures of dispersion, the scores on the seven GHCS subscales were examined for patterns of integrated (i.e., similarities) and differentiated (i.e., variability) culture within the organisations. Results: Patterns of differentiated culture were found in six organisations for one or more GHCS subscales. Patterns of integrated culture were found in three organisations for one subscale. In two organisations, patterns of both integrated and differentiated culture were found. Conclusions: The findings contribute to the conceptualisation of and research into organisational culture in group homes, with implications for changing and maintaining culture.